The Obligation of National Courts Against Whose Decision There Is No Judicial Remedy to Refer Questions to the Court of Justice of the European Union - NEAMÈš, Valentin Paul (Journal of Legal Studies, 2016)
The present paper presents the obligation that courts in the member states of the European Union have to refer questions to the Court of Justice of the European Union, with a focus on courts against whose decision there is no judicial remedy under national law. The paper starts by presenting the applicable framework regarding the preliminary reference procedure, then focuses on analyzing the exceptions to national court’s duty under article 267 TFEU, with a focus on the direction in which the case law is heading based on the most recent judgments handed down by the Court of Justice of the European Union in 2015, finally presenting the author’s conclusions and observation on the subject.